(untitled) - Lee, Daniel O'C. (Oxford, 1992)
Describes all cultured crustaceans of commercial significance--lobsters, crayfish, crabs, spiny lobsters, shrimps, prawns. Explores current standards for determining the feasibility and desirability of culture proposals. Coverage extends from broadstock acquisition and management through the operation of hatcheries, nurseries and on-growing units to key aspects of processing and marketing. Compares investment and operating costs of different culture options. Analyzes recent trends in world crustacean markets for economic and financial appraisal along with the role of crustacean culture within the economics of developing nations.
Keywords: Crustacea,Shellfish culture,Shellfish trade; Economic aspects